Metal Halide Solid-State Surface Treatment for High Efficiency PbS and PbSe QD Solar Cells - Crisp, Ryan; Kroupa, Daniel M.; Marshall, Ashley R.; Miller, Elisa M.; Zhang, Jianbing; Beard, Matthew C.; Luther, Joseph M. (Scientific Reports, 2015)
We developed a layer-by-layer method of preparing PbE (E=S or Se) quantum dot (QD) solar cells using metal halide (PbI2, PbCl2, CdI2, or CdCl2) salts dissolved in dimethylformamide to displace oleate surface ligands and form conductive QD solids. The resulting QD solids have a significant reduction in the carbon content compared to films treated with thiols and organic halides. We find that the PbI2 treatment is the most successful in removing alkyl surface ligands and also replaces most surface bound Cl- with I-. The treatment protocol results in PbS QD films exhibiting a deeper work function and band positions than other ligand exchanges reported previously. The method developed here produces solar cells that perform well even at film thicknesses approaching a micron, indicating improved carrier transport in the QD films. We demonstrate QD solar cells based on PbI2 with power conversion efficiencies above 7%.